Oculomotor Nerve Palsy Due to Unusual Causes. Issue 2 (June 2021) - Tian, Guohong; Kardon, Randy; Feng, Chaoyi; Hong, Rujian; Sha, Yan; Sun, Xinghuai; Wang, Min
Abstract : Background: An isolated oculomotor nerve (CN III) palsy is a diagnostic concern because of the potential for serious morbidity or life-threatening causes. We present 5 unusual causes of oculomotor nerve palsy that escaped initial diagnosis in order to raise awareness of their associated features that will facilitate correct diagnosis. Methods: This study consisted of a retrospective analysis of clinical features and imaging of 5 patients who were referred for neuro-ophthalmologic evaluation with presumed diagnosis of oculomotor nerve palsy of unknown reasons. Results: A complete CN III palsy and an inferior division CN III palsy were diagnosed with a schwannoma in the cavernous sinus and orbital apex portion, respectively; a middle-aged woman with aberrant regeneration was found to have a small meningioma; an adult man with ptosis was diagnosed with cyclic oculomotor paresis with spasms; and a patient after radiation was diagnosed with neuromyotonia. Conclusions: Localizing the lesion of oculomotor nerve palsy and careful examination of the imaging is crucial. Aberrant regeneration, cyclic pupil changes, and past medical history of amblyopia, strabismus, or radiation are also very helpful for diagnosis. Abstract : Supplemental Digital Content is Available in the Text.